The Book of Psalms in the Church Slavonic Language from Norov´s Book Collection - Celunova, Jelena (Slavistica Vilnensis, 2020)
This article is devoted to the research of the Book of Psalms manuscript from A. S. Norovʼs book collection stored in the Department of manuscripts of the Russian State Library. The manuscript is written in the beginning of the 18th century in Church Slavonic language Polish letters. This manuscript has never been studied before, it is nonetheless of interest primarily as a Latin-graphic text, which is a transliteration of the originals in Church Slavonic. Very few such texts have survived, and almost all of them were created in the Grand Duchy of Lithuania. The article provides a complete description of the manuscript and analyses of its language peculiarities. The analysis has made it possible to identify Church Slavonic protographs of the manuscript, and also to establish that the manuscript was written by women (most likely nuns) for private use. Since the authors of the transliteration themselves had very good command of Church Slavonic, it can be assumed that the text was written to order. Against the background of the cultural and historical context of the turn of the 17th and 18th centuries it can be assumed that the manuscript was written by the nuns of one of the southwestern Russian Uniate monasteries who had moved to one of the monasteries in Russia at that time.
Keywords: the Book of Psalms; Church Slavonic language; Polish language; Latin-graphic text; Grand Duchy of Lithuania; Basilian Monastery